Aplikasi metode magnetik untuk identifikasi sebaran bijih besi di Kabupaten Solok Sumatera Barat - Aufi Maslihah Umamii; Tony Yulianto; Dadan Dani Wardhana (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
The aim of this research is to identify the subsurface structure in Solok West Sumatera by mapping the magnetic field. The measurement was made at 821 points in Solok, West Sumatra to obtain total magnetic field. Data processing was carried out by the daily variation correction and correction IGRF (International Geometric Reference Field) on magnetic field anomaly data to obtain the anomaly contour of total magnetic field. Furthermore, the upward continuation process and reduction to pole process were applied to obtain the contour of local and regional anomaly. The result showed a pair of positive and negative closure which is then created a 2D model and 3D model using the software Geosoft Oasis Montaj. The 2D modeling showed that the subsurface structure with one of rock layer has a susceptibility of 0.185 and 0.196 cgs which is strongly suspected as iron ore mineral carrier rock. This rock layer is a unit of limestone derived from the Perem-age Barisan Formation. 3D modeling was used to calculate iron ore reserves in Solok, which is estimated to reach 1.414.579.375 ton.Keyword: magnetic field anomaly, susceptibility of rocks, iron ore, 2-D, 3-D.